Korelasi perencanaan obat dengan pemenuhan ketersediaan obat di Puskesmas Provinsi Kepulauan Riau - Indri Ayu Ningsih; Wina Aumeilia (Jurnal Archipelago, 2024)
Correlation of drug planning compare to drug availability is part of drug management activities which has an important role to prevent drug excesses in Community Health Centers. The aim of this research is to determine the correlation and description of drug management at the planning stage and fulfilling drug availability at the Community Health Center in Riau Islands Province. This research is an observational study that is descriptive qualitative in nature through observation using data on drug availability in Community Health Centers in Riau Islands Province. Quantitative data was obtained by tracing 2024 drug planning data, drug availability Riau Islands Province 2024. Data analysis was carried out by evaluating drug availability data and linked to drug planning. The results of the research show that there is a correlation between drug planning in the community health centers Riau Islands Province and the description of drug availability with an achievement of 96.65%.